Determinants of Stock Return and Firm Value of Manufactures Listed at the Indonesian Stock Exchanges - Afriyani Afriyani; Nurfatwa Andriani Yasin; Agussalim Rahman (MIX: JURNAL ILMIAH MANAJEMEN, 2023)
Objectives: This study aimed to examine the impact of ownership structure, fundamental factors, and technical analysis on stock returns, as well as the impact of these factors on firm value.Methodology: This research is an explanatory descriptive research with a quantitative approach where the study encompasses a population of 148 manufacturing companies listed on the Indonesia Stock Exchange. From this population, a purposive sample of 50 companies is selected for in-depth analysis.Finding: The findings indicated that the ownership structure did not have a substantial impact on stock returns, despite showing a positive trend. Similarly, fundamental factors were found to have a positive influence on stock returns but the effect was not statistically significant. In contrast, the utilization of analytical techniques was associated with a significant and positive impact on stock returns. Additionally, the study revealed that ownership structure, fundamental factors, analytical techniques, and stock returns collectively had a noteworthy and positive effect on firm value. Finally, the investigation demonstrated that ownership structure, fundamental factors, and technical analysis played a significant role in determining firm value through their impact on stock returns.Conclusion: Overall, the company's value can be significantly enhanced through stock returns by considering ownership structure, fundamental factors, and technical analysis in a positive manner.